WEST SUMATERA PROVINCE’S READNINESS TO INITIATE FOREIGN AFFAIRS - Rika Isnarti; Poppy Irawan (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2022)
This paper analyzes the readiness of the West Sumatra provincial government in establishing foreign affairs. This study identified perceptions and implementation of foreign affairs conducted by the regional government of West Sumatra province. Furthermore, this Research is expected to map the challenges, opportunities, and obstacles faced by the regions in formulating foreign affairs. This Research uses a qualitative approach in processing and analyzing data collected through interviews with stakeholders in the government level of West Sumatra province and collection of policy documents on West Sumatra provincial government related to foreign affairs. The results show that the West Sumatra provincial government is not fully prepared to carryout foreign affairs. The regional government of the province of West Sumatra continues to improve it self to prepare its institutions to establish and run foreign affairs. Then, the government aware that local government has support central government in doping foreign affairs. It has various obstacles for the implementation of foreign affairs such as human resources, mechanisms, and limitations of local government initiatives to follow kupon foreign Cooperation carried out by the central government.